THE ROLE OF CUSTOMER TRUST AS MEDIATOR BETWEEN PRODUCT QUALITY, PRICE, AND PURCHASE DECISION AMONG EIGER ADVENTURE CUSTOMERS - Chaidir, John; Zulfikar, Taufik; Aprianti, Ine; Millah, Fadli (Faculty of Economic and Business, University of Pasundan, 2025)
This study aims to examine the influence of Product Quality and Perceived Price on Purchase Decision, with Customer Trust as a mediating variable. A quantitative approach was used through a survey method involving 200 EIGER Adventure customers in Bandung. Data were analyzed using Structural Equation Modeling (SEM) with the aid of AMOS 24 software. The sample size was set at 250 respondents, meeting the minimum requirement of 5–10 times the number of indicators used in SEM analysis. The results indicate that both Product Quality and Perceived Price have a positive and significant effect on Customer Trust and Purchase Decision. Furthermore, Customer Trust also has a positive influence on Purchase Decision and mediates the effect of Product Quality and Perceived Price on Purchase Decision. These findings emphasize the crucial role of Customer Trust in transforming product value into actual purchasing decisions. Although Product Quality may not directly drive purchase decisions, it plays a vital role in building trust.